(3GdRghQ GdeJbWaI ef JGQjN ecI GdeTQaIs - (3eMeO Hf CMeO Hf Ydj, Jbj GdOjf, CHh GdWjH Gdecqj GdMSfj, J (B832 (3g` s ((3UGdM eMeO Hf UGdM s)
(3ChdgG (B:s
(3CeG HYO agPG eG hYOJ HPcQg ai cJGHi GdYbO GdKejf ef CNHGQ ecI GdeTQaI s
(3BNQgG (B:s
(3hGdCTYGQ ai GdJThb Edi gPg GdeTGYQ GdTQjaI cKjQI , hGddg CYde s
(3Vef eLehY s
(3YdjgG JhbjY UGdM Hf eMeO Hf eMeO Hf UGdMs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B224 s
Keywords: (3GdJGQjNs